Cost-effectiveness of gastrostomy placement for children with neurodevelopmental disability. Issue 10 (2nd May 2008) - Townsend, J L; Craig, G; Lawson, M; Reilly, S; Spitz, L
Abstract : Introduction: Malnutrition and growth deficiency are common in neurologically impaired children. Gastrostomy placement has been shown to result in significant catch-up growth, improved health of the child and reduction in family stress; its cost-effectiveness has not been investigated. Aims: Costs related to gastrostomy placement are estimated here from a prospective controlled study of children referred to a tertiary paediatric centre in the UK. Methods: Costs of inpatient stay, medication, tests, general practitioner consultations, community healthcare, equipment, and parents' indirect costs were estimated at baseline and follow-up. Costs of the different types of gastrostomy surgery are given. Results: Results for both time periods were available for 54 of the 76 children recruited to the study. Five-day food diaries were kept at baseline and follow-up. Costs of food increased slightly but not significantly post surgery from £33 to £40 (€44 to €54, US65 to US78) per week. Variation in cost between cases was considerable but the mean net cost difference of £20.80 (CI −£43.79 to £85.35) (€28 (CI €−59 to €115), US41 (CI US−86 to US167)) per week per child including for food and surgery, was also not significant. Community service costs were significantly lower post surgery. Few parents reported personal costs at either time point, although many had reduced or stopped paid work to care for the child. Conclusion: As gastrostomy placement for these children resulted in significant clinical benefit at no significant extra cost, it is concluded that the procedure is cost-effective.